Focal Region Ray Tracing of Conventional and Shaped Lens Antenna - Muhsin, M.; Kamardin, Kamilia; Yamada, Yoshihide (International Journal of Integrated Engineering, 2023)
Multibeam lens antennas are useful for 5G mobile communication systems. For multibeam design, feed position determination of specified lens becomes an important subject. The feed position data can be obtained from focal region ray tracing. In this paper, a simple and convenient ray tracing method by using the MATLAB function of “polyxpoly” is proposed. To evaluate the program, focal region ray tracing on conventional hyperbolic planar, spherical convex, and Abbe’s sine condition lens are presented in this paper. For focal region ray tracing, parallel incident ray is considered. The incident ray’s angle is changed from 0 degree to 30 degrees with an interval of 10 degrees. On hyperbolic planar and spherical convex lenses, ray concentration at the focal region is distorted at incident angle of 10 degrees and above. On Abbe’s sine condition lens, good concentration is maintained until 20 degrees. Concentration points agree well with the theoretical value. Therefore, the correctness of the program is ensured.